(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study examines how shifting consumer behavior and growing pet ownership influence the pet grooming industry. It focuses on factors that guide pet owners’ choices such as product type, service format, and environmental impact, and reflects the strong emotional bond between pets and their owners. Insights from this analysis aim to help grooming providers tailor offerings to evolving customer expectations. This study employs a descriptive research design with purposive sampling to select 30 pet owners. A structured questionnaire assessed preferences for grooming products (organic vs. conventional), service modalities (in‑salon vs. mobile grooming), pricing, and hygiene standards. Collected data were analyzed using weighted means to rank the relative importance of each preference factor. Based on the results of the above-mentioned variables, the pet owners obtained an overall weighted mean of 3.30. In light of these findings, the researchers recommend the use of organic and eco-friendly grooming products, as well as the adoption of mobile grooming services. Findings indicated that high‑quality, safe products and stringent hygiene practices were primary drivers of customer satisfaction. The strong preference for organic and eco‑friendly products highlighted environmental and health concerns among pet owners. Convenience factors, particularly mobile grooming, were valued for saving time and reducing pet stress. It was recommended that grooming businesses prioritize premium, eco‑friendly product lines, maintain rigorous cleanliness standards, and expand mobile service offerings to align with consumer preferences.